East of Malta, west of Suez : the admiralty account of the naval war in the eastern mediterranean, September 1939 to March 1941 : prepared for the Admiralty (London: His Majesty's Stationery Office, 1943)
"by the Ministry of Information Bibliotheek Camille Huysmans"